Finding 'public purpose' in 'subtitled oddities': Framing BBC Four's Danish imports as public service broadcasting. Issue 2 (1st September 2013) - Ward, Sam
This article looks at the success of Danish drama imports on BBC Four from the specific perspective of public service broadcasting's definition in the globalized era. It argues that the presentation of the service offered by BBC Four to the national audience has come to be significantly inflected by its importation strategy in such a way that openly co-opts, rather than resists or obscures, cross-border flows. While the BBC faces budgetary cuts and a statutory obligation to avoid bidding wars for imported content, their Danish equivalent Danmarks Radio (DR) offers a source of affordable and consistent drama. The article looks first at the institutional and economic characteristics of DR to show how these imports are formed with both the international market and public service intentions as central concerns. It then demonstrates, by drawing on interviews with BBC acquisitions personnel and press coverage, how these imports have been framed in such a way that ensures their integration with the explicit 'public purpose' of BBC Four's remit.